2023
DOI: 10.1002/pat.6158
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a copper hydroxystannate functionalized graphene oxide for rigid polyvinyl chloride foam toward improved fire safety

Abstract: A copper hydroxystannate (CHS) functionalized graphene oxide (GO) (CHS@GO) was feasibly prepared through an in‐situ method, and well characterized by TEM, XRD, FTIR and XPS. Rigid poly vinyl chloride (RPVC) foams containing CHS@GO were prepared by utilizing methyl hexahydrophthalic anhydride and isocyanate as coupling agents, azodiisobutyronitrile and azodicarbonamide as blowing agents. The fire safety, mechanical properties and thermal decomposition behavior of the RPVC foams were studied. The RPVC foam conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
(86 reference statements)
0
1
0
Order By: Relevance
“…From the spectrum of the char of EC/10DQ, almost no additional absorption peaks emerged, which indicated that DQ mainly played a role in the gas phase. 27 For EC/7DQ3CuHS, the absorption peak at 1105 cm −1 belonged to Sn-O bending vibration, 19 and the broad absorption peak around 638 cm −1 corresponded to the stretching vibration of Cu-O, 28 which were similar to the peaks appeared in EC/10CuHS.
Figure 4.(a) FTIR and (b) XRD results of the char of pure EC and its composites.
…”
Section: Resultsmentioning
confidence: 68%
“…From the spectrum of the char of EC/10DQ, almost no additional absorption peaks emerged, which indicated that DQ mainly played a role in the gas phase. 27 For EC/7DQ3CuHS, the absorption peak at 1105 cm −1 belonged to Sn-O bending vibration, 19 and the broad absorption peak around 638 cm −1 corresponded to the stretching vibration of Cu-O, 28 which were similar to the peaks appeared in EC/10CuHS.
Figure 4.(a) FTIR and (b) XRD results of the char of pure EC and its composites.
…”
Section: Resultsmentioning
confidence: 68%